5m-2-9m-3=7+m+23

Simple and best practice solution for 5m-2-9m-3=7+m+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m-2-9m-3=7+m+23 equation:


Simplifying
5m + -2 + -9m + -3 = 7 + m + 23

Reorder the terms:
-2 + -3 + 5m + -9m = 7 + m + 23

Combine like terms: -2 + -3 = -5
-5 + 5m + -9m = 7 + m + 23

Combine like terms: 5m + -9m = -4m
-5 + -4m = 7 + m + 23

Reorder the terms:
-5 + -4m = 7 + 23 + m

Combine like terms: 7 + 23 = 30
-5 + -4m = 30 + m

Solving
-5 + -4m = 30 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
-5 + -4m + -1m = 30 + m + -1m

Combine like terms: -4m + -1m = -5m
-5 + -5m = 30 + m + -1m

Combine like terms: m + -1m = 0
-5 + -5m = 30 + 0
-5 + -5m = 30

Add '5' to each side of the equation.
-5 + 5 + -5m = 30 + 5

Combine like terms: -5 + 5 = 0
0 + -5m = 30 + 5
-5m = 30 + 5

Combine like terms: 30 + 5 = 35
-5m = 35

Divide each side by '-5'.
m = -7

Simplifying
m = -7

See similar equations:

| 3x+5x-4=9x-6 | | 3x^3=4x^2+15x | | 30-7n=10n-4 | | x^2-4y^2+8x+16y-100=0 | | 23-2x=49 | | 2(4x+5)=5x-14 | | (5x+9)(2x-7)= | | 3x+5x-4=9-6 | | -7(-8+4m)=-140 | | 8x+6-3x=4x-7 | | f(x)=2x^3+2x^2-18x-18 | | Mx+7mx=7 | | 2(5x-14)=4x+5 | | 3(4y+27)+y=-23 | | 2.5(1.2y+6)=1.92+8(4.3y+2.42) | | 4-6x+8=1-5x+4 | | 11-7m=-4(4m+4) | | 11.8+7n=9.5-4n | | P=4x-12 | | S-31=20.3 | | 1/8b=-12 | | 3x+2=22x-2 | | ((30*x)/2*x) | | 9x-8+2x=15x | | -2/3=-10 | | 2.4z+1.2z-6.4=0.7 | | 1/3x-7/12x=2/3 | | 3x^2-7x-16=0 | | 30x/2x | | 10x+15=6.5x-13 | | -16y+40-y=-2y+4 | | -2.6d-0.49=-1.79 |

Equations solver categories